Design, synthesis and biological evaluation of novel potent MDM2/p53 small-molecule inhibitors. Issue 2 (15th January 2015) - Ivanenkov, Yan A.; Vasilevski, Sergei V.; Beloglazkina, Elena K.; Kukushkin, Maksim E.; Machulkin, Alexey E.; Veselov, Mark S.; Chufarova, Nina V.; Chernyaginab, Elizaveta S.; Vanzcool, Anton S.; Zyk, Nikolay V.; Skvortsov, Dmitry A.; Khutornenko, Anastasia A.; et al.
Graphical abstract: Abstract: Regioselective synthesis, biological evaluation and 3D-molecular modeling for a series of novel diastereomeric 2-thioxo-5 H -dispiro[imidazolidine-4, 3-pyrrolidine-2, 3-indole]-2, 5(1 H )-diones are described. The studied compounds have been tentatively identified as potent small molecule MDM2/p53 PPI inhibitors and can therefore be reasonably regarded as promising anticancer therapeutics.